A Real-World, Multicenter, Observational Retrospective Study of Durvalumab After Concomitant or Sequential Chemoradiation for Unresectable Stage III Non-Small Cell Lung Cancer - Bruni, Alessio; Scotti, Vieri; Borghetti, Paolo; Vagge, Stefano; Cozzi, Salvatore; D’Angelo, Elisa; Giaj Levra, Niccolò; Fozza, Alessandra; Taraborrelli, Maria; Piperno, Gaia; Vanoni, Valentina; Sepulcri, Matteo; et al. (Frontiers in Oncology, 2021)
Introduction For unresectable stage III NSCLC, the standard therapy consists of chemoradiation (CRT) followed by durvalumab maintenance for responding patients. The present study reports on the safety and outcome of durvalumab use after CRT in a real-world, multi-center, retrospective cohort. Methods Two hundred thirty-eight patients have been included. We collected data on systemic therapy, radiation therapy, the timing between CRT and durvalumab, number of durvalumab cycles, reasons for non-starting or discontinuation, incidence, and grade of adverse events (AEs), progression-free and overall survival. Results One-hundred fifty-five patients out of 238 (65.1%) received at least one durvalumab dose; 91 (58.7%) after concomitant (cCRT) and 64 (41.3%) after sequential CRT (sCRT), respectively. PD-L1 status was unknown in 7/155 (4.5%), negative in 14 (9.1%), and positive ≥1% in 134/155 (86.4%). The main reasons for non-starting durvalumab were: progression (10.1%), PD-L1 negativity (7.5%), and lung toxicity (4.6%). Median follow-up time was 14 months (range 2-29); 1-year PFS and OS were 83.5% (95%CI:77.6-89.7) and 97.2% (95%CI:94.6-99.9), respectively. No significant differences in PFS or OS were detected for cCRT vs. cCRT, but the median PFS was 13.5 months for sCRT vs. 23 months for cCRT. Potentially immune-related AEs were recorded in 76/155 patients (49.0%). Pneumonitis was the most frequent, leading to discontinuation in 11/155 patients (7.1%). Conclusions In conclusion, durvalumab, given as maintenance therapy, for stage III unresectable NSCLC patients respondingto concurrent or sequential CRT, resulted to be associated with very promising short-term survival rates also in a large multi-center, retrospective, real-world series. Durvalumab is confirmed to be the first drug obtaining a survival benefit over CRT within the past two decades, and the present study contributes to validating its use in clinical practice.